2018
DOI: 10.1073/pnas.1710901115
|View full text |Cite
|
Sign up to set email alerts
|

MYCN -amplified neuroblastoma maintains an aggressive and undifferentiated phenotype by deregulation of estrogen and NGF signaling

Abstract: SignificanceHigh-risk neuroblastoma (NB), a cancer of the sympathetic nervous system, is challenging to treat. MYCN is frequently amplified in high-risk NB and is linked to an undifferentiated phenotype and poor prognosis. Estrogen and nerve growth factor (NGF) are inducers of neural differentiation, a process associated with a favorable disease. We show that MYCN suppresses estrogen receptor alpha (ERα) and thereby NGF signaling and neural differentiation. ERα overexpression is sufficient to interfere with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 63 publications
5
50
0
Order By: Relevance
“…1d). It was reported that NGFR was downregulated by MYCN amplification to maintain an undifferentiated and more aggressive phenotype 20 . SNCG is traditionally characterized as a neuronal marker which is highly expressed in peripheral sensory neurons 21 .…”
Section: Hypoxia Represses Ra-induced Neuron Differentiation Markers mentioning
confidence: 99%
“…1d). It was reported that NGFR was downregulated by MYCN amplification to maintain an undifferentiated and more aggressive phenotype 20 . SNCG is traditionally characterized as a neuronal marker which is highly expressed in peripheral sensory neurons 21 .…”
Section: Hypoxia Represses Ra-induced Neuron Differentiation Markers mentioning
confidence: 99%
“…Current therapy for neuroblastoma, involves surgery, chemotherapy, monoclonal antibody treatment, and radiotherapy 38 with efficacy of each treatment depending on the disease stage and its biological features 39 . Surgery alone may achieve remission of MYCN-amplified neuroblastoma if it remains localized 38 but usually patients receive 13-cis-retinotic acid treatment to induce neuronal differentiation 40 and maintain a minimal residue disease 41 although patients frequently develop 13-cis-retinotic acid resistance leading to relapse 42 . Anti-GD2 antibody therapies combined with granulocyte macrophage colony stimulating factor (GM-CSF), interleukin-2 (IL-2) and 13-cis-retinotic acid have improved the 2-year survival rate by 20% 40,43,44 , but neuroblastoma cells with low GD2 expression fail to respond to this therapy 45 and so the prognosis of high-risk neuroblastoma remains very poor 43,46 and new treatments are required.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a large number of studies have demonstrated that the MYCN gene is closely related to neuroblastoma . A study by Zaatiti et al indicated that neuroblastoma IMR‐32 cell lines had significantly decreased proliferation ability after MYCN knockout .…”
Section: Discussionmentioning
confidence: 99%